An Investigation of Titanium/Silicon Oxide‐CNTs Anode Material for Lithium‐Ion Batteries. Issue 5 (3rd February 2020) - Zhang, Wenshan; Li, Wensheng; Zhou, Xiaoping
Abstract: Discovering a high‐performance (high rate capability, high specific capacity, and good stability) anode material for automobile battery applications is a great challenge. A titanium/silicon oxide‐CNTs (Ti m Si n Ol ‐CNTs) is synthesized and tested as anode material for lithium‐ion batteries. High specific capacity (278 mAhg −1 at 100 mA g −1 ), high rate capability (156 mAh g −1 at 4000 mA g −1 ), and good stability (maintains 278 mAhg −1 after 200 cycles) are reached over Ti m Si n Ol ‐CNTs. The as‐synthesized Ti m Si n Ol ‐CNTs has a particle structure that Ti m Si n Ol encapsulates CNTs with CNTs ends stretching out of the particles. In the Ti m Si n Ol phase, the TiO2 crystal seeds are formed and encapsulated in amorphous SiO y boundaries, which have sub‐nano pores. The high performance properties of Ti m Si n Ol ‐CNTs could come from the synergetic combination of (1) the excellent electronic conductivity of CNTs and the amorphous carbon in Ti m Si n Ol ‐CNTs, (2) the high Li + intaking capability of the TiO2 crystal seeds, (3) the high electrochemical activity of SiO y, (4) the high Li + insertion/extraction kinetics in the small TiO2 crystal seeds and the amorphous SiO y with sub‐nano pores, and (5) the high volume change tolerance offered by the CNTs binder and the amorphous SiO y . Abstract : A double trap : A Ti m Si n Ol ‐CNTs anode material is synthesized for lithium‐ion batteries. Ti m Si n Ol ‐CNTs has a typical structure in which anatase TiO2 crystal seeds are encapsulated in amorphous silicon oxides, while the CNTs are encapsulated in silicon oxides and titanium oxides. The CNTs and the amorphous carbon (formed from the decomposition of ethylene glycol) in the material forms the electronic conductive network. The specific structure of the material provides it with high rate capability, high specific capacity, and long cycling life‐time.